Realisme dalam Sastra Dunia: Kajian Sastra Bandingan - Sumarwati K Poli (SUSASTRA: Jurnal Ilmu Susastra dan Budaya, 2005)
Comparative Literature as an approach remains an issue that raises some questions since the term itself is rather abstract. Marc Bloch stated the establishment of the term Comparative Literature itself that a new self-awareness – la prise de conscience – was born. Such awareness resulted from the evolution of local languages and ways of thinking in response to geopolitical changes (Jost 1974), a new curiosity to find out what is different and what is similar among literary texts, and why they are different despite their common origin. Therefore, comparative literary studies is close to the studies of world literature inasmuch as they often compare one particular aspect or more of literary works coming from different cultures and expressed in different languages. In foreign languages, the term Comparative Literature generally refers to the same meaning, but in German, vergleichende Literaturewissenschaft (Pichois Rousseay 1967: 12) underlines the disciplines’ scientific action on account of its methods. In this article, the focus discussion is on the mimetic aspect, that is, how reality is revealed through literature, especially on the thematic and methodical levels, in novels that are categorized as realistic works based on the assumption that realism in literature emerged as consequence of the growth of capitalism (Lukacs 1972) in France, Britain, and Indonesia. As long as there is cross-cultural human communication. Comparative studies of literature will keep on taking place as an activity that contributes to mutual understanding.Kata kunci: kajian bandingan, realisme, latar, tema